ChemInform Abstract: Remazol‐Catalyzed Hydroperoxyarylation of Styrenes. Issue 51 (December 2015) - Chen, Ying‐Ho; Lee, Ming; Lin, Yi‐Zhen; Leow, Dasheng
Abstract: A variety of hydroperoxides are obtained under mild reaction conditions by carbooxygenation of styrenes using RBBR as novel photosensitizer and air as molecular oxygen source.